2017
DOI: 10.1126/scitranslmed.aai8030
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine kinase blocking collagen IV–derived peptide suppresses ocular neovascularization and vascular leakage

Abstract: Vascular endothelial growth factor (VEGF)–neutralizing proteins provide benefit in several retinal and choroidal vascular diseases, but some patients still experience suboptimal outcomes, and the need for frequent intraocular injections is a barrier to good outcomes. A mimetic peptide derived from collagen IV, AXT107, suppressed subretinal neovascularization (NV) in two mouse models predictive of effects in neovascular age-related macular degeneration (NVAMD) and inhibited retinal NV in a model predictive of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 55 publications
4
34
0
Order By: Relevance
“…This is particularly important as, in addition to its role in promoting vascular leakage by inhibiting Tie2 phosphorylation, Ang2 also promotes inflammation by enhancing the effects of TNFα. We have previously shown that Ang2 overexpression alone was sufficient to increase leakage in retinal vessels [ 28 ] and, here, we demonstrate that Ang2 can enhance TNFα-mediated permeability relative to TNFα alone ( Figure 5 B). These data are consistent with the observations that the release of Ang2 stored within ECs by TNFα sensitizes ECs to TNFα stimulation [ 24 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This is particularly important as, in addition to its role in promoting vascular leakage by inhibiting Tie2 phosphorylation, Ang2 also promotes inflammation by enhancing the effects of TNFα. We have previously shown that Ang2 overexpression alone was sufficient to increase leakage in retinal vessels [ 28 ] and, here, we demonstrate that Ang2 can enhance TNFα-mediated permeability relative to TNFα alone ( Figure 5 B). These data are consistent with the observations that the release of Ang2 stored within ECs by TNFα sensitizes ECs to TNFα stimulation [ 24 ].…”
Section: Discussionsupporting
confidence: 74%
“…AXT107 is a non-RGD 20-mer α v β 3 and α 5 β 1 integrin-binding peptide that has previously been shown to inhibit VEGF signaling and stimulate Tie2 through the conversion of the normally inhibitory Ang2 into an activator [ 28 , 29 ]. When injected into the eye, the effects of AXT107 are sustained over a period of at least two months through the formation of a slow-release gel in the vitreous [ 28 ]. Furthermore, intraocular injection of AXT107 strongly suppresses VEGF-induced vascular leakage, but also reduces vascular leakage induced by intraocular injection of lipopolysaccharide (LPS) [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, achieving a sustained suppression of neovascularization would necessitate some form of sustained delivery, such as a microparticle-based delivery system that encapsulates nanoparticles formulated with a therapeutic peptide; 12 in addition, a therapeutic peptide has been shown to form a natural depot upon injection and that is slowly released from the depot. 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“… 12 Recently, a collagen IV–derived peptide has been demonstrated in several animal models to significantly reduce neovascularization and vascular leakage. 13 To reduce the frequency of injections and to prolong the action of the antiangiogenic peptides, peptide-containing microparticles that slowly release peptide over an extended period of time can be injected to provide sustained inhibition of neovascularization and vascular leakage. Effective antiangiogenic agents including small molecule tyrosine kinase inhibitors, peptides, antibodies, siRNAs, or genes can be intraocularly delivered as treatment.…”
mentioning
confidence: 99%
“…However, chemical lesion, anoxia, or inflammation disrupts the balance between angiogenic and anti-angiogenic factors. Capillaries invade from the limbal vascular plexus, leading to the occurrence of corneal neovascularization [2-4]. Neovascular capillaries are often accompanied by bleed or contract, eventually leading to blindness [5, 6].…”
Section: Introductionmentioning
confidence: 99%